The Influence of Canadian Intellectuals’ Ideological Views on the Political Culture in Canada at the Beginning of the 20th Century - SOKOV I.A. (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2014)
The article analyses the political views of Canadian intellectuals which had influence on the formation of Canadian political culture at the turn of the 20th century. The author confirms that the Canadian intellectual thought was the main ideological factor in the conditions of the formation of Canadian statehood, undeveloped party and political system, the lack of deep traditions of the parliamentary system, insufficient political practice and the lack of distinct ideology of basic political parties in the process of forming the Canadian nation. On the basis of studied Canadian sources, the author makes conclusion that the most of Canadian intellectuals did not participate directly in the political process and they considered themselves its bystanders. Besides, the Canadian intellectuals promoted the British political culture of the Victorian epoch. Although all of them were familiar wih the British socialistic thought – Fabianism, they insisted that the social transformation in the Canadian society is possible only through the improvement of moral system, the education of lower social classes and the maintenance of elite monarch traditions. The American influence on Canadian political culture was peripheral at the beginning of the 20th century. The ideas of the Chicago Sociological School and the European continental thought were not used. The Victorian intellectuals understood their time as the social crisis and their political discussions were often devoted to the problems of imperialism, religion, education and feminism. They undoubtedly influenced the Canadian political elite in the matter of further development of the Canadian nation and state, but they expressed their own unique views on the contemporary society in academic press and in elite clubs discussions. They did not share the opinion of publicity about contemporary social processes, because their position was far from the direct party policy. Though some of them participated as the experts in the government commissions and in the international organizations, and doing so, they influenced the process of making political decisions. The Canadian Victorian intellectuals considering themselves bystanders of contemporary social processes, created the background for smooth evolution transition to the policy of social transformation, the development of unique Canadian liberal tradition and the creation of the social welfare state in the middle of the 20th century.